HUBUNGAN KONSEP DIRI DENGAN MOTIVASI BERPRESTASI SISWA KELAS IV SD GUGUS I KECAMATAN AMPENAN - Rahayu, Diah; Darmiany, Darmiany; Nurhasanah, Nurhasanah (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2019)
This study aims to determine the relationship between self-concept and achievement motivation among fourth-grade students at SDN Cluster I, Ampenan District, in the 2019/2020 academic year. The research used a quantitative approach with a correlational method. Instruments included self-concept and achievement motivation questionnaires, both of which were tested for validity and reliability. The study involved 120 students from four elementary schools. Data analysis was conducted using normality, linearity, and Pearson Product Moment correlation tests. The results indicate a significant and positive relationship between self-concept and achievement motivation, with a correlation coefficient of 0.705 and a contribution of 49.7%. This implies that the higher the students’ self-concept, the higher their achievement motivation.